Food Composition in The Stomach of Selais Bungkuk (Hemisilurus heterorhynchus) in The Kampar Kiri River, Mentulik Village, Riau Province - Roza Elvyra; Nurul Hakiki; Yusfiati Yusfiati; Khairijon Khairijon; Imelda Wardani (Jurnal Biologi Tropis, 2023)
Food Composition in The Stomach of Selais Bungkuk (Hemisilurus heterorhynchus) in The Kampar Kiri River, Mentulik Village, Riau Province